Analysis and Design of an Advanced Para Rubber Information System in Adherence to the Rubber Control Act 1999 for Rubber Supply Chain Management - Pinitjitsamut, Montchai; Sammapun, Usa; Bunyakiati, Panuchart (วารสารอิเล็กทรอนิกส์การเรียนรู้ทางไกลเชิงนวัตกรรม, 2024)
To effectively oversee and manage Para rubber across the supply chain at the national level, the Government of Thailand issued the Rubber Control Act in 1999 and declare the Notification No. 13 in 2019 mandating collection of rubber plantation and trade information in order to regulate rubber industry and support nationwide strategic decision-making. However, challenges exist concerning data incompleteness and inconsistencies as well as information linkage since collected information is scattered among various government bodies overseeing rubber-related activities. The primary objective of this study is thereby to explore and adopt technologies for integrating scattered Para rubber information as well as to analyze and design a rubber information system to streamline data collection and data utilization in adherence to the provisions outlined in the Rubber Control Act of 1999 and Notification No. 13. The rubber information system analysis and design include analyzing rubber supply chain information, designing a system prototype, and developing a blueprint that facilitates operational procedures by systematically gathering data from transactions occurring at various stages of the rubber supply chain, encompassing farmers, trade dealers, manufacturers, and exporters. When the design and the prototype provided by this study are developed, key entities that manage Thailand's overall Para rubber can leverage the rubber information system and the integrated rubber information for strategic and well-informed decision-making.